2013
DOI: 10.1105/tpc.113.110783
|View full text |Cite
|
Sign up to set email alerts
|

MIXTA-Like Transcription Factors and WAX INDUCER1/SHINE1 Coordinately Regulate Cuticle Development inArabidopsisandTorenia fournieri   

Abstract: The waxy plant cuticle protects cells from dehydration, repels pathogen attack, and prevents organ fusion during development. The transcription factor WAX INDUCER1/SHINE1 (WIN1/SHN1) regulates the biosynthesis of waxy substances in Arabidopsis thaliana. Here, we show that the MIXTA-like MYB transcription factors MYB106 and MYB16, which regulate epidermal cell morphology, also regulate cuticle development coordinately with WIN1/SHN1 in Arabidopsis and Torenia fournieri. Expression of a MYB106 chimeric repressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
226
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(232 citation statements)
references
References 63 publications
6
226
0
Order By: Relevance
“…However, the most striking result is that the dull fruit aspect of tomato cuticle mutants appears primarily due to different epidermal cell differentiation. The relationship between epidermal cell differentiation and cuticle development is now well established and genes controlling both cell morphogenesis and cuticle synthesis have been identified (Kurdyukov et al, 2006;Javelle et al, 2011;Oshima et al, 2013). More indirect effects may also arise from perturbations in fruit cell division and development that affect cuticle formation in tomato fruit (Czerednik et al, 2012).…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the most striking result is that the dull fruit aspect of tomato cuticle mutants appears primarily due to different epidermal cell differentiation. The relationship between epidermal cell differentiation and cuticle development is now well established and genes controlling both cell morphogenesis and cuticle synthesis have been identified (Kurdyukov et al, 2006;Javelle et al, 2011;Oshima et al, 2013). More indirect effects may also arise from perturbations in fruit cell division and development that affect cuticle formation in tomato fruit (Czerednik et al, 2012).…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propmentioning
confidence: 99%
“…Coordinated regulation of metabolic pathways controlling cuticle formation has been demonstrated for transcription factors of the SHINE/WAX-INDUCER family (Aharoni et al, 2004;Broun et al, 2004) and recently for MIXTA-like myeloblastosis (MYB) transcription factors (Oshima et al, 2013). Several of their downstream targets involved in cutin synthesis, modification, and assembly, as well as in cell wall formation and structure and in epidermal cell patterning (Shi et al, 2013), have been identified.…”
mentioning
confidence: 99%
“…Using these mutant lines, we showed that MYB106 and MYB16 are required for the formation of cuticle nanoridges in petals and stamens. Furthermore, we reported that MYB106 is sufficient for the ectopic production of nanoridges (Oshima et al 2013a). However, plants over-expressing MYB106 exhibit severe dwarfism and are not suitable for commercial production.…”
mentioning
confidence: 91%
“…Additionally, the genes encoding these transporters are expressed in epidermal cells (Bird et al 2007;Luo et al 2007;Panikashvili et al 2007;Pighin et al 2004). The expression of ABCG12, CYP77A6, and CYP86A4 is suppressed in loss-of-function lines, but induced in gain-of-function lines involving the MYB106/NOECK MIXTA-like transcription factor (TF), which regulates cuticle production (Oshima et al 2013a).…”
mentioning
confidence: 99%
See 1 more Smart Citation